Application of gamma and electron beam irradiation for chestnuts conservation - Carocho, Márcio (2013)
Due to the distribution of low quality products, adulteration, counterfeit on the Ukrainian market, the widening of export-import supplies, it is too important to develop criteria and methods for the identification domestic and exported food products, detection of adulteration, techniques and methods assessing quality and early spoilage screening of food products using modern express methods of analysis. Such method is an electronic nose system based on chemical sensors, for example, piezoelectric quartz microweighing, combined with complex computer algorithms registration, processing and decision making («artificial intelligence»). Odor is one of the most significant parameters among the sensory properties of foods. The representative flavor of volatile compounds, so-called fingerprint, may provide knowledge about safety and particular characteristic of food, acting sometimes as an indicator of process mistake as well. Off-flavors may include substances originating from the metabolism of spoilage microorganisms, bacteria and fungi; which may naturally or accidentally contaminate the products during their production. Electronic noses (EN) are instruments based on an array of semi low selective sensors that are selected on the chemical affinity to individual components of the analyzed gas mix and vapors and pattern recognition methods. ENs have been applied in various food contexts such as process monitoring, freshness evaluation, shelf-life investigation, authenticity determination, and product traceability. The object of our research is express methods development of identification, estimation of quality and early spoilage screening of dairy and meat products using multisensory electronic nose system based on piezosensors. The absolute advantages of electronic sensory analyzers are their versatility, portability, ability to automate measurements and interpretation of signals, reproducibility of results.